Photoproduction of K*Σ in an effective Lagrangian approach - Huang Fei; Wang Ai-Chao; Wei Neng-Chang (EPJ Web of Conferences, 2024)
All the available data on differential cross sections, total cross sections, spin density matrix elements, and parity spin asymmetry for the γp → K*+Σ0 and γp → K*0Σ+ reactions are analyzed within an effective Lagrangian approach. The reaction amplitudes are constructed by considering the s-channel exchanges of N, Δ, and their excited states, the t-channel exchanges of K, K*, and κ, the u-channel exchanges of Λ, Σ, and Σ* , and the interaction current. Two fits with different reaction mechanisms are obtained that describe the data equally well. The s-channel Δ(1905)5=2+ resonance exchange is found to provide dominant contributions in both fits. The t-channel κ exchange only contributes significantly to γp → K*0Σ+ in model II, which challenges the claim made in literature that the available parity spin asymmetry data supports the dominant contribution of κ exchange in γp → K*0Σ+.